2021
DOI: 10.3390/foods10010075
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Bread Fortification by Grape Pomace Powder: Nutritional, Technological, Antioxidant, and Sensory Properties

Abstract: Grape pomace powder (GPP), a by-product from the winemaking process, was used to substitute flour for wheat bread fortification within 0, 5, and 10 g/100 g. Rheological properties of control and fortified doughs, along with physicochemical and nutritional characteristics, antioxidant activity, and the sensory analysis of the obtained bread were considered. The GPP addition influenced the doughs’ rheological properties by generating more tenacious and less extensible products. Concerning bread, pH values and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 59 publications
10
102
3
Order By: Relevance
“…Each annotated compound is reported in Table S1, together with its abundance values and composite mass spectrum. Tolve et al [11], analyzing the same experimental breads, showed that the inclusion of higher levels of GPP caused an increase in the total dietary fiber content. The total dietary fiber content represents a key point when targeting the bioactive profile of a certain cereal-based food product.…”
Section: Changes Of Phenolic Bioaccessibility During the In Vitro Digmentioning
confidence: 99%
See 4 more Smart Citations
“…Each annotated compound is reported in Table S1, together with its abundance values and composite mass spectrum. Tolve et al [11], analyzing the same experimental breads, showed that the inclusion of higher levels of GPP caused an increase in the total dietary fiber content. The total dietary fiber content represents a key point when targeting the bioactive profile of a certain cereal-based food product.…”
Section: Changes Of Phenolic Bioaccessibility During the In Vitro Digmentioning
confidence: 99%
“…After baking and cooling, breads were cooled (i.e., room temperature) and kept in airtight food storage plastic bags. The chemical composition of major ingredients and the resulting breads has been reported elsewhere [11].…”
Section: Ingredients and Bread Preparationmentioning
confidence: 99%
See 3 more Smart Citations